2002
DOI: 10.1186/1471-2407-2-17
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral gene transfer of angiostatic ATF-BPTI inhibits tumour growth

Abstract: Background: The outgrowth of new vessels -angiogenesis -in the tumour mass is considered to be a limiting factor of tumour growth. To inhibit the matrix lysis that is part of the tumour angiogenesis, we employed the chimeric protein mhATF-BPTI, composed of the receptor binding part of the urokinase (ATF) linked to an inhibitor of plasmin (BPTI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Independently of the vector system selected, the tumor response ranges from sufficient [8,9,10,11,12,13,14,16] to no response [25]. A previously published study reported a heterogeneous tumor response of different breast-cancer cell lines within the same tumor model [17], suggesting tumor cell-dependent differences in susceptibility to endostatin treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Independently of the vector system selected, the tumor response ranges from sufficient [8,9,10,11,12,13,14,16] to no response [25]. A previously published study reported a heterogeneous tumor response of different breast-cancer cell lines within the same tumor model [17], suggesting tumor cell-dependent differences in susceptibility to endostatin treatment.…”
Section: Discussionmentioning
confidence: 97%